The role of framing mechanisms in explaining system-wide change: The case of the Northern Ireland conflict and peace process - Murphy, Joanne; Denyer, David; Pettigrew, Andrew (Wiley, 2020)
System‐wide change is often challenging to achieve due to complex and fragmented institutions, dispersed and diffused power structures, confidence‐sapping histories of failure and the influence of multiple and overlapping fields. This study examines how a large complex system‐wide problem such as the Northern Ireland Conflict and Peace Process was paradoxically opened up and made more receptive to change by widening of the way the problem was framed. We demonstrate how and why the framing enables the mobilization of cooperation and the delivery of contextually appropriate collective action critical to the achievement of outcomes in system‐wide change processes. More specifically, we examine how and why such complex and precarious processes emerge over extended timescales through four mechanisms: frame contesting, reframing, frame reproduction and frame defending. Each of these mechanisms is agentic, dynamic, purposive and politically charged. The time‐series analysis of these interlinked mechanisms is a crucial and innovative feature of the study. We encourage management and organizational scholars to elevate their gaze to the system‐wide changes so emblematic of contemporary society and offer an outline agenda for research.
Keywords: Northern Ireland Conflict and Peace Process; system‐wide change processes